Nis Programme - Object of Art Development of Research Skills and Student Interpretation Competencies. - KULANOVA, FARIZA; DANIYAR, BAITUREYEV; SINGH, CHANDAN PAL (International Journal of Multidisciplinary Research and Studies, 2023)
The research area is concerned with the development of the student's research abilities and interpretative competency through various art-related assignments. The importance of studying the subject "Art" in the educational programmer NIS-program is that art is a means of self-expression for the student, while art teaching is the student's interaction with the environment through the language of Fine Arts, a comprehensive sense of the world. In addition, research issues were chosen, and methodologies were devised based on the student's abilities and age. Learning approaches designed through sources improve learning efficacy. The study's significance was decided, and it was carried out to the best of its ability. Students gained research skills and an interest in experimenting as a consequence of the study. The study's successful elements are highlighted, and recommendations for further research are made.